Climate change adaptation strategies for Egypt’s agricultural sector: A ‘suite of technologies’ approach - Perez, Nicostrato D.; Kassim, Yumna; Ringler, Claudia; Thomas, Timothy S.; ElDidi, Hagar (International Food Policy Research Institute, 2021)
Climate change negatively affects Egypt’s agriculture sector. This brief summarizes the results of a modeling exercise to examine a range of climate change adaptation approaches to counteract agricultural productivity declines. Rather than simulating a single technology, a ‘suite of technologies’ approach was used. For several food crops, none of the technology suites, individually or in combination, are shown to counteract the adverse impacts of climate change. For these crops, which include maize, oilseeds, pulses, and sugar, even stacking of technologies will not return productivity to pre-climate change levels. However, for fruits and vegetables, potatoes, rice, and wheat, crops less adversely affected by climate change, increased investments in climate changeresponsive crop traits, soil fertility improvement, water management, crop protection, or a combination of these technologies can counteract the adverse impacts of climate change on agricultural productivity. From a perspective, strong cooperation with the rest of the world on climate change adaptation will ultimately benefit Egyptian consumers. Doing so will reduce disruption of global food markets, which is of particular importance for countries, like Egypt, that are well integrated into those markets. In particular, Egypt’s economy and all Egyptian consumers benefit from the importation of lower-value, high water-consuming cereals under the hotter and drier conditions that can be expected in Egypt in the future due to climate change.